The Role of Urodynamics in the Potential Recipients of Kidney Transplantation - Wicaksono P, Marshal Harvy; De Niro, Agustin J. Nanda (PT FORMOSA CENDEKIA GLOBAL, 2024)
Urodynamics plays a vital role during the pre-transplant evaluation of potential kidney transplant recipients. This evaluation is useful in diagnosing existing urologic conditions and increasing the success rate of the transplantation through proactive management that can reduce the risk of long-term complications. This paper explains the role of urodynamics prior to kidney transplantation (KT) by elaborating on the rationalization of testing on the potential KT recipients. In addition, it reviews some recommendations from recent studies. Until now, scholars still seek an agreement regarding the criteria of patients that must perform a formal urological evaluation using urodynamics before undergoing a transplant. Studies reported mixed results regarding the criteria, although they generally advocated its usage. Nevertheless, introducing patients with a risk score for urological problems can be an alternative to grouping them before performing urodynamics. This step enables medical staff to group and prioritize patients who need in-depth urological evaluation using urodynamics.